MIDWAY TO DIGITAL TRANSFORMATION OF MEDICAL EDUCATION: CURRENT PERCEPTION AND ADAPTATION OF MEDICAL STUDENTS TOWARDS SYNCHRONOUS ONLINE LECTURES - Tan, Giovanna Renee; Utomo, Prattama Santoso; Suhoyo, Yoyo; Hidayah, Rachmadya Nur (Universitas Gadjah Mada, 2023)
Background: The Covid-19 pandemic had forced majority of medical institutions to cease face-to-face learning and implement online synchronous technology. Thus, the improvement of online synchronous learning had become a priority for the continuity of medical education. This study explored students’ self-regulated online learning behavior and perception towards synchronous online learning during the Covid-19 pandemic.Methods: This study used a cross-sectional mixed-method design. Stratified random sampling was applied for participant recruitment that included 101 participants, whom are medical students from academic year 1 to 3 (2018-2020) . A total of 12 interview participants were recruited purposively to allow adequate representation of each batch. Data were collected using a modified Self-regulated Online Learning Questionnaire-Revised and a semi-structured interview. Descriptive statistics and thematic analysis were used for data analysis.Results: Approximately 72.28% of participants (N = 101) were of the higher self-regulated online learning behavior group. Batch 2019 had the highest percentage of higher-self regulated learning participants (27.72%, n = 35, p = 0.899). The environmental structuring average score was the highest (x̄ = 5.77), while persistence domain was the lowest (x̄ = 5.03). The participants appreciated the use of technology to provide quality lectures and flexibility of attending lectures. However, classroom interaction and accountability was a major challenge.Conclusion: Synchronous online lectures have the potential to allow students find their effective study time and method during the Covid-19 pandemic.